Who Wants Gender When You Can Have Sex? - Lucy Garrido (Revista Estudos Feministas, 2003)
Based on an overview about the definition of both network and work within feminist movement networks, and about some of the last regional coordination experiences, the article sets out the question: “Articulation: how, where from and what for”. Three large working guidelines are suggested, that, in several cases, guide or might guide regional feminist action. Insertion in World Social Forum takes part of the incidence strategy that Marcosur Feminist Articulation has adopted in order to answer this question. And election of subject matter and style of the campaign “Your mouth, fundamental against fundamentalisms”, is a way to respond to the one that says: “who wants gender, when one can have sex?”